2014
DOI: 10.1111/den.12283
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endoscopic retrograde cholangiopancreatography using a newly developed short‐type single‐balloon endoscope in patients with altered gastrointestinal anatomy

Abstract: Background and Aim: Endoscopic approaches for pancreatobiliary diseases in patients with altered gastrointestinal anatomy had been impractical until the development of balloonassisted endoscope (BAE) made it feasible. The aim of the present study was to evaluate the usefulness of a newly developed short-type single-balloon endoscope (s-SBE) for endoscopic retrograde cholangiopancreatography (ERCP) in patients with altered gastrointestinal anatomy. Methods: From March 2013 to November 2013, s-SBE-assistedERCP w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 35 publications
1
36
0
1
Order By: Relevance
“…Performing ERCP in patients with SAGA poses a greater risk of complications than in patients with normal anatomy . Recently, several papers also reported that the occurrence of adverse events in such patients using several‐type BAE was 0–17% from small‐size sample studies, and yet, there are few reports from a large‐scale study . In our previous study using C‐short DBE, we reported 5% .…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Performing ERCP in patients with SAGA poses a greater risk of complications than in patients with normal anatomy . Recently, several papers also reported that the occurrence of adverse events in such patients using several‐type BAE was 0–17% from small‐size sample studies, and yet, there are few reports from a large‐scale study . In our previous study using C‐short DBE, we reported 5% .…”
Section: Discussionmentioning
confidence: 74%
“…Performing ERC for pancreatobiliary diseases in patients with SAGA is considered challenging because of the difficulty of scope insertion to the blind end and ERC‐related interventions. Up to date, there are several studies reporting on more usefulness of BAE for postoperative pancreatobiliary diseases in comparison with conventional endoscopes . Martin Raithel et al reported the success rate of reaching the blind end was 16.2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A standard balloon enteroscope has a 200-cm long and 2.8-mm diameter channel. However, the recently developed short single-balloon enteroscope has a 152-cm long and 3.2-mm diameter channel, which allows for all kinds of regular ERCP accessories [12,13]. The differences between the endoscopes used for D-ERCP are summarized in Table 2.…”
Section: Device-assisted Ercpmentioning
confidence: 99%
“…Endoscopic retrograde cholangiopancreatography (ERCP) for patients with surgically altered gastrointestinal anatomy remains challenging. Recently, short‐type double‐balloon endoscopes (DBE) for pancreaticobiliary interventions in patients with surgically altered anatomy have become available in many institutions . Success rates of reaching the target site and of ERCP‐related interventions associated with use of these endoscopes are reported to range between 73% and 100% and between 85% and 100%, respectively .…”
Section: Introductionmentioning
confidence: 99%